Seasonal Liquidity, Rural Labor Markets, and Agricultural Production - Fink, Günther; Jack, B. Kelsey; Masiye, Felix (American Economic Review, 2020)
Rural economies in many developing countries are characterized by a lean season in the months preceding harvest, when farmers have depleted their cash and grain savings from the previous year. To identify the impacts of liquidity during the lean season, we offered subsidized loans in randomly selected villages in rural Zambia. Ninety-eight percent of households took up the loan. Loan eligibility led to increases in on-farm labor and agricultural output, driving up wages in local labor markets. Larger effects for poorer households suggest that liquidity constraints contribute to inequality in rural economies. (JEL O13, O15, O18, Q11, Q12, R23)